The effect of Allium sativum (Garlic), Allium cepa (Onion) and Aloe barbadensis miller (Aloe vera) against Bacterial Leaf Blight (BLB) on rice caused by xanthomonas oryzae pv. oryzae / Nurul Hedaya Jamaluddin - Jamaluddin, Nurul Hedaya (Faculty of Plantation and Agrotechnology, 2018)
Rice is known as a staple food that consumed by more than 3 billion people around the world because it provides 21% of energy and 15% of protein requirements. Bacterial Leaf Blight (BLB) of rice caused by Xanthomonas oryzae pv. oryzae (Xoo), an important constraint to rice production in Asia. The extent of yield loss could be 30% to 50% depends on the growth stage of the crop, cultivar, season climatic condition and level of nitrogen application. The present study was conducted to isolate and identify the Xoo and also to determine the effectiveness of garlic, onion and aloe vera towards bacterial leaf blight on rice in vitro assay. The infected leaf samples were plated on nutrient agar and gave light yellow, sticky, round and smooth bacterial colonies, it showed that it was gram negative bacteria. Chemical control of the disease may contribute to environmental pollution. Use of botanicals in control of plant disease is more safe and eco-friendly. Three plant extracts at different concentration (0%, 25%, 50% and 100%) were tested for their antibacterial activity. Antimicrobial activity of aqueous plant extract was determined by agar well diffusion method on nutrient agar medium. Among these extracts, garlic was most effective against Xoo which at 100% concentration it caused inhibition of the bacterium (25.84%) at moderate rate.